Useful plants from Campo Rupestre recorded by naturalists: the example of Serra do Gandarela, Minas Gerais - Juliana Loureiro de Almeida Campos; Aparecida Vieira de Almeida, Carolina; Luiza da Silva, Priscila; Nunes Junior, Tarcisio Tadeu; Lins Brandão, Maria das Graças (Gaia Scientia, 2024)
Brazil has a diverse flora and rich sociobiodiversity, but few native plants are used in home medicine or as active ingredients in medicines and other commercial products. This fact is a consequence of the process of genetic loss to which native vegetation has been subjected since the beginning of Portuguese colonization, leading to a decrease in traditional knowledge associated. This article presents information on the traditional use of native plants that occur in the brazilian Cerrado (campo rupestre) and documented by naturalists based on the flora of Serra do Gandarela, Minas Gerais. The plants were identified through lists present in documents produced by the Serra do Gandarela National Park team and information on traditional uses and the naturalists were extracted from the Dataplamt database. The PubMed database was used to identify research that validated the plants presented in this work. Eighty native plants distributed in Serra do Gandarela had their uses documented by 13 naturalists, 50 of which were subjected to validation studies. The medicinal category presented the highest number of records. The importance of these species for the development of bioproducts and the conservation of biodiversity and associated traditional uses is discussed.